Endodontic Treatment and Esthetic Management of a Geminated Central Incisor Bearing a Talon Cusp - Elif Tarım Ertaş; Meral Yırcalı Atıcı; Hakan Arslan; Bilal Yaşa; Hüseyin Ertaş (Case Reports in Dentistry)
Gemination with talon cusps is an uncommon morphologic dental anomaly, characterized by the formation of clinically wide tooth that can cause significant aesthetic and clinical problems including esthetic impairment, pain, caries susceptibility, and tooth crowding. These morphological dental anomalies have specific treatment needs due to the abnormal morphology and need virtuous radiologic diagnosis. Multidisciplinary approach can supply success of the treatment plan that can provide esthetic and occlusal requirements. In this case report, the multidisciplinary approach for the treatment of geminated tooth with talon cusp is presented with the clinical and radiographic findings.